y+2=-3(x+6)

Simple and best practice solution for y+2=-3(x+6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y+2=-3(x+6) equation:


Simplifying
y + 2 = -3(x + 6)

Reorder the terms:
2 + y = -3(x + 6)

Reorder the terms:
2 + y = -3(6 + x)
2 + y = (6 * -3 + x * -3)
2 + y = (-18 + -3x)

Solving
2 + y = -18 + -3x

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-2' to each side of the equation.
2 + -2 + y = -18 + -2 + -3x

Combine like terms: 2 + -2 = 0
0 + y = -18 + -2 + -3x
y = -18 + -2 + -3x

Combine like terms: -18 + -2 = -20
y = -20 + -3x

Simplifying
y = -20 + -3x

See similar equations:

| F=-9c+80 | | 4x-10+11X=180 | | 6-v=157 | | -7/8x2 | | (105x+9.5)=(14.75) | | 4x-15+11X=180 | | 12+6p+3q-5p+7p-2= | | 8x-16+3x-8=4x | | 5y+4=4w+5 | | -6+(-2x)=10*2-x | | 1.54/1.1 | | -0.571429(x-0.25)=0.428571 | | 32=3y-3+2y | | 3x+5+6x=77 | | 6(-1+5x)=294 | | 5p+3q=-25 | | 7x-4=3x+14 | | 9x-(3x+6)=7x-24 | | (x-2)/x=120 | | 10x+14+y+46=180 | | 4x-7+7x-24=68 | | 7x-4=3x+18 | | 106/34=x/9 | | -14=-6x+4x-4 | | -28=-2y | | 12(m-935)=660 | | 1+5x-3x=-11+6x | | 7.7x-13.3=56 | | 2x+8=5x-3+2x+1+x+6 | | 6x+7y=162 | | 810=27(z+6) | | -4(6x+7)=316 |

Equations solver categories